2007
DOI: 10.1007/s00127-007-0276-y
|View full text |Cite
|
Sign up to set email alerts
|

A little knowledge: Caregiver burden in schizophrenia in Malawi

Abstract: In this population, knowledge about schizophrenia was associated with higher caregiver burden. This does not prove that knowledge causes burden, but suggests that cultural factors may mediate the relationship between knowledge and burden, and that care is needed when introducing caregiver education in new cultures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
1
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 31 publications
2
24
1
2
Order By: Relevance
“…These findings are supported by previous studies which indicated that higher burden was associated with an increased number of hours spent caring for the family members with mental illness [18, 27]. When the responsibilities of caring for the family members with mental illness are distributed over more than one member of the family, the burden is expected to be much less [28–30]. Accordingly, in the current study, “Worrying” was highest among caregivers living in families with relatively fewer members (<6 members).…”
Section: Discussionsupporting
confidence: 84%
“…These findings are supported by previous studies which indicated that higher burden was associated with an increased number of hours spent caring for the family members with mental illness [18, 27]. When the responsibilities of caring for the family members with mental illness are distributed over more than one member of the family, the burden is expected to be much less [28–30]. Accordingly, in the current study, “Worrying” was highest among caregivers living in families with relatively fewer members (<6 members).…”
Section: Discussionsupporting
confidence: 84%
“…Higher educational level appears to provide an advantage to the caregivers. It is speculated that better knowledge give rise to better capability to cope with their caregiving task as well as other stressors in life (10,43). Caregivers with higher education possibly have more secured job and stable financial income that reduce the financial burden on caregiving task, thus improving their satisfaction for lives.…”
Section: Discussionmentioning
confidence: 99%
“…Although some sources argue that caregiver burden will decrease as the caregivers' level of knowledge on the disease increases (15,16), there are also studies showing that family burden increases as the level of knowledge of the disease increases (17). When deciding on the roadmap in the process of preparing support programs for patients and their families, it is important to know the factors associated with caregiver burden.…”
Section: Introductionmentioning
confidence: 99%